2020
DOI: 10.1103/physreva.101.032310
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of matrix product states into quantum circuits of one- and two-qubit gates

Abstract: Matrix product state (MPS) belongs to the most important mathematical models in, for example, condensed matter physics and quantum information sciences. However, to realize an N -qubit MPS with large N and large entanglement on a quantum platform is extremely challenging, since it requires high-level qudits or multi-body gates of two-level qubits to carry the entanglement. In this work, an efficient method that accurately encodes a given MPS into a quantum circuit with only one-and two-qubit gates is proposed.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…It has also been shown that TN-based architectures have deep connections to the building of QML models [109]. Specifically, we show that it is possible to encode a quantum-inspired TN architecture, such as MPS, into a quantum circuit with single-and two-qubit gates [110].…”
Section: Tensor Networkmentioning
confidence: 79%
“…It has also been shown that TN-based architectures have deep connections to the building of QML models [109]. Specifically, we show that it is possible to encode a quantum-inspired TN architecture, such as MPS, into a quantum circuit with single-and two-qubit gates [110].…”
Section: Tensor Networkmentioning
confidence: 79%
“…The present QMPS framework requires the quantum state to be accessible at each time step for both training and inference purposes; yet, quantum states are not observable in experiments without performing expensive quantum state tomography. Nevertheless, there already exist efficient encoding strategies that map MPS into quantum circuits [61][62][63]. Moreover, several proposals were recently developed in which MPS are harnessed for quantum machine learning tasks, for example as part of hybrid classical-quantum algorithms [64,65] or as classical pre-training methods [66,67].…”
Section: Discussion/outlookmentioning
confidence: 99%
“…For example, optimization of TN states with use of a quantum circuit was proposed in Refs. [230,231]. Also, a combination of the variational quantum eigensolvers 232,233) and the TN formalism is expected to become important in connection with quantum chemistry problems.…”
Section: Other Trends and Prospects Of Tensor Networkmentioning
confidence: 99%